Exterior wall heat insulation leveling gel and preparation method thereof

CN122916596APending Publication Date: 2026-10-16GUANGDONG MUFENG YIJU NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611205410.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]本发明为克服上述现有技术所述的无机硅基保温浆料储运易分层沉降、厚涂层易收缩开裂、无裂纹自修复能力且仅依靠孔隙隔热难以阻隔外墙红外蓄热、常规分步改性工艺制备流程繁琐等缺陷,提供一种外墙隔热保温找平凝胶;

Benefits of technology

本发明制备的外墙隔热保温找平凝胶桶装储存稳定性优异,低温冻融循环后无变质、结块,可实现5 mm厚层顺畅批刮施工,表干时间仅2 h,养护3 h无初期干燥裂纹,施工适配性强;产品导热系数低至0.028 W/(m·K)。产品以无机粘结基体为主,VOC仅24 g/L、甲醛16 mg/kg,苯系物、氨等有害物质释放量均远低于国标限定;燃烧性能达到A (A2)级不燃,燃烧增长速率指数仅56.9 W/s,600 s总放热量仅3.5 MJ,防火安全等级高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the field of building thermal insulation coating, and discloses a kind of outer wall heat insulation leveling gel and its preparation method.The gel contains lithium silicate aqueous solution, hydroxyl-terminated methylsiloxane prepolymer, hierarchical hollow ceramic microbeads, silica aerogel, nano lanthanum hexaboride, boron-modified siloxane microcapsule and other components by mass fraction.The present application adopts vacuum airtight sanding integrated process, and the grinding process synchronously activates the filler and the bonding phase hydroxyl, and in-situ condensation forms organic-inorganic interpenetrating network matrix.The product is storage stable, thick layer construction has no early crack, the thermal conductivity is as low as 0.028 W / (m·K), A2 grade is not flammable, the water immersion bonding strength retention rate is 93%, the sunning heat insulation cooling effect is excellent, solves the problems of traditional silicon-based slurry easy delamination and cracking, no self-repair, poor infrared heat insulation and complicated preparation process, and is suitable for high solar radiation building outer wall integrated thermal insulation leveling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermal insulation coatings, and more specifically, to an external wall thermal insulation and leveling gel and its preparation method. Background Technology

[0002] In the field of building exterior wall insulation, rock wool and polystyrene boards have shortcomings such as detachment and fire resistance, while cement mortar is prone to cracking due to its own weight. Precast inorganic silicon-based leveling and insulation gel has become the mainstream research and development direction. Existing improvement solutions can only optimize general conventional properties such as adhesion and basic thermal conductivity, and cannot overcome the core contradiction of multiple properties being mutually restrictive.

[0003] Patent CN117229678A discloses an inorganic silicon sound insulation and thermal insulation gel, which uses silicate-styrene-acrylic emulsion composite bonding and binary spherical thermal insulation filler. This system contains a large amount of organic components, which are prone to aging after long-term high-temperature service and have poor fire resistance stability; it relies solely on the pores of the filler for thermal insulation and has no infrared radiation blocking capability; under the normal pressure stepwise mixing process, the filler density varies greatly, the finished product is prone to delamination when left to stand, and the thick coating retains air bubbles, forming thermal bridges. It is only suitable for thin coating conditions and cannot be used for thick-layer leveling of exterior walls with large height differences.

[0004] Patent CN116855117A discloses a lithium silicate thermal insulation coating, which uses lithium silicate to improve the efflorescence defect. However, the product needs to be diluted with water before application and cannot be leveled in one piece. The thermal conductivity of the hydrophilic aerogel used is significantly reduced after it comes into contact with water. The coating is prepared by stirring at normal pressure, and the curing cycle of a 10 mm coating is as long as 7 days. It relies solely on the passive crack resistance of the substrate and has no ability to compensate for or repair microcracks. The post-ultrasonic process only breaks up agglomerates in the short term and easily damages the functional powders, making it impossible to stabilize the paste in the long term.

[0005] In summary, while existing technologies can achieve conventional indicators such as water resistance and basic thermal insulation, they still have the following problems: relying solely on pore insulation is insufficient to reduce infrared heat storage in exterior walls; there is no self-healing mechanism for cracks, resulting in continuous degradation of thermal insulation performance after long-term use; and the atmospheric pressure preparation process cannot simultaneously achieve long-term non-delamination of the finished product and short-cycle curing of thick coatings. Summary of the Invention

[0006] To overcome the shortcomings of the prior art, such as the easy stratification and sedimentation of inorganic silicon-based thermal insulation slurry during storage and transportation, the easy shrinkage and cracking of thick coatings, the lack of self-healing ability of cracks, the difficulty in blocking infrared heat storage of external walls by relying solely on pore insulation, and the cumbersome preparation process of conventional step-by-step modification, this invention provides an external wall thermal insulation and leveling gel. Another objective of this invention is to provide a method for preparing an external wall thermal insulation and leveling gel.

[0007] To solve the above-mentioned technical problems, the technical solution of the present invention is as follows: An exterior wall thermal insulation and leveling gel, by weight, comprises the following components: 42-55 parts of lithium silicate aqueous solution, 8-10 parts of hydroxyl-terminated methylsiloxane prepolymer, 10-18 parts of graded hollow ceramic microspheres, 8-14 parts of trimethylsilyl-terminated silica aerogel, 3-6 parts of hollow glass microspheres, 2-5 parts of flaky muscovite, 1-3 parts of nano-lanthanum hexaboride, 2-4 parts of boron-modified siloxane microcapsules, 2-5 parts of lithium magnesium silicate, and 0.3-1 parts of inorganic dispersant.

[0008] Furthermore, in the external wall thermal insulation and leveling gel, graded hollow ceramic microspheres and hollow glass microspheres contact each other to form a skeleton structure, and sheet-like white mica is interspersed in the gaps of the skeleton structure; lithium silicate aqueous solution and hydroxyl-terminated methylsiloxane prepolymer are covalently condensed to form an interpenetrating network adhesive matrix.

[0009] Furthermore, the graded hollow ceramic microspheres contain the following particle sizes: 150~200 μm, 75~150 μm, and 30~75 μm.

[0010] Preferably, 150~200 μm accounts for 65wt%~75%, 75~150 μm accounts for 15wt%~22%, and 30~75 μm accounts for 10wt%~13%.

[0011] Preferably, the trimethylsilyl-terminated silica aerogel has a D90 of 15-20 μm; the flaky muscovite has a D50 of 5-10 μm; the nano-lanthanum hexaboride has a particle size of 30-80 nm; and the boron-modified siloxane microcapsules have a particle size of 20-50 μm.

[0012] Preferably, the inorganic dispersing agent includes sodium hexametaphosphate and sodium pyrophosphate.

[0013] Furthermore, the lithium silicate aqueous solution has a solid mass fraction of 32% to 35%, and the molar ratio of silicon dioxide to lithium oxide is 3.2 to 4.0.

[0014] Furthermore, the number-average molecular weight of the hydroxyl-terminated methylsiloxane prepolymer is 1200~4500.

[0015] A method for preparing the aforementioned exterior wall thermal insulation and leveling gel includes the following steps: S1. Stir and mix the lithium silicate aqueous solution and hydroxyl-terminated methylsiloxane prepolymer until homogeneous; S2. Add graded hollow ceramic microspheres, trimethylsilyl-terminated silica aerogel, hollow glass microspheres, flake mica, nano lanthanum hexaboride, lithium magnesium silicate, and inorganic dispersing agents, and perform vacuum closed sand milling using zirconia grinding balls with a particle size of 3~5 mm. S3. After cooling the system, add boron-modified siloxane microcapsules and stir to mix. S4. Sealed and constant temperature curing to obtain external wall thermal insulation and leveling gel.

[0016] Furthermore, the S2 vacuum sand mill has a linear speed of 2.5~3.2 m / s and a sand milling time of 8~12 min.

[0017] Preferably, the surfaces of the S2 post-graded hollow ceramic microspheres, trimethylsilyl-terminated silica aerogels, hollow glass microspheres, and sheet-like muscovite are all grafted with silane molecular layers.

[0018] Preferably, the vacuum degree of the S2 vacuum mill is -0.06 MPa to -0.09 MPa, and the temperature of the milling system is controlled at 30 to 45°C.

[0019] Preferably, after cooling the system to below 40°C in step S3, boron-modified siloxane microcapsules are added and stirred.

[0020] Preferably, S4 is aged at 25~35℃ for 12~24 h.

[0021] Further, the preparation method of the boron-modified siloxane microcapsules includes the following steps: hydroxyl-terminated methylsiloxane, organotin catalyst, trimethyl borate, and oil phase emulsifier are mixed evenly to obtain an oil phase; melamine-formaldehyde prepolymer, boric acid, and anionic emulsifier are dissolved in deionized water, and the pH of the system is adjusted to 7.5-8.0 to obtain an aqueous phase; the oil phase is added to the aqueous phase, and shear emulsification is performed to form an oil-in-water emulsion, which is then stirred to stabilize the emulsion system; staged heating polymerization is performed to first form a primary capsule wall, and then the silanol and boronol groups in the system undergo covalent condensation to form a hybrid capsule wall; after purification and sieving, the boron-modified siloxane microcapsules are obtained.

[0022] Furthermore, the temperature is first raised to 53~57℃ and held for 1.2~1.8 h to form the primary capsule wall, and then the temperature is raised to 65~70℃ and held for 2.5~3.5 h to carry out the covalent condensation of silanol and boronol.

[0023] Preferably, the oil phase emulsifier is one or both of Span-60 and Span-80; the anionic emulsifier is one or both of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.

[0024] Furthermore, the shear emulsification speed is 750~850 r / min, and the emulsification time is 10~15 min; the stirring speed for stabilizing the emulsion is 250~300 r / min.

[0025] Preferably, the purification process includes aging, centrifugation, water washing, alcohol washing, vacuum drying, and sieving to obtain the boron-modified siloxane microcapsules.

[0026] Preferably, the process involves aging at room temperature for 4 hours, centrifugation, washing with water three times, washing with ethanol once, vacuum drying at 40°C, and sieving.

[0027] Conventional systems rely solely on the addition of silane and aluminate coupling agents for filler pretreatment and modification. The sand milling process only serves to break up filler agglomerates, failing to simultaneously achieve matrix crosslinking and filler interface anchoring. In contrast, this invention utilizes the controllable mechanical friction of vacuum-sealed sand milling to form an integrated synergistic reaction system. This eliminates the need for separate filler modification, filtration, and drying processes. The system uses lithium silicate as the main binder phase, combined with hydroxyl-terminated methylsiloxane prepolymers, which simultaneously activate the hydroxyl groups on the surfaces of various fillers and binder phases under grinding and shear friction. This leads to in-situ covalent condensation, constructing an organic-inorganic interpenetrating network matrix. The bonding layer alleviates the inherent defects of pure lithium silicate materials, such as high rigidity and easy shrinkage and cracking, which is different from the conventional improvement methods in the industry that simply add organic emulsions and short-cut fibers for physical toughening. At the same time, the graded hollow ceramic microspheres and hollow glass microspheres overlap to form a continuous and sealed heat-insulating skeleton. The sheet-like white mica is interspersed in the gaps of the skeleton to evenly disperse the curing shrinkage stress. The compounded magnesium silicate precisely controls the rheological properties of the paste. The gap between the filler and the matrix interface is eliminated by grinding and in-situ bonding, which fundamentally avoids the agglomeration and sedimentation of the filler during long-term static storage. Therefore, the product is uniform and stable when stored in drums and does not deteriorate or clump during low-temperature cycling.

[0028] Compared with the prior art, the beneficial effects of the technical solution of the present invention are: The exterior wall thermal insulation and leveling gel prepared by this invention exhibits excellent stability in bucket storage, showing no deterioration or clumping after low-temperature freeze-thaw cycles. It allows for smooth application of 5 mm thick layers, with a surface drying time of only 2 hours and no initial drying cracks after 3 hours of curing, demonstrating strong adaptability to various construction methods. The product has a low thermal conductivity of 0.028 W / (m·K). The product is primarily composed of an inorganic binder matrix, with VOCs of only 24 g / L and formaldehyde of 16 mg / kg. The release of harmful substances such as benzene compounds and ammonia is far below the national standard limits. Its combustion performance reaches Class A (A2) non-combustible, with a combustion growth rate index of only 56.9 W / s and a total heat release of only 3.5 MJ over 600 s, demonstrating a high level of fire safety.

[0029] The product has a low dry density, a bonding strength of 0.58 MPa with cement mortar substrate, and a compressive strength of 1.4 MPa, demonstrating reliable mechanical load-bearing performance. After a 14-day extended immersion test, the bond strength retention rate reaches 93%, and the coating shows no obvious whitening, powdering, or peeling, exhibiting outstanding water resistance and durability. After 90 days of standing at room temperature in sealed containers, the layer thickness is less than 1 mm, and stirring for 3 minutes restores the uniform paste, overcoming the defects of sedimentation and clumping in conventional slurries during storage and transportation. The self-healing strength recovery rate of cracks reaches 87%, and minor cracks can self-repair, effectively preventing the degradation of thermal insulation performance over long-term use. After 50 cycles of hot and cold temperatures, no visible cracks are found in the coating, and the temperature on the back of the substrate is controlled to 42.6℃ after 4 hours of simulated irradiation, demonstrating significant advantages in thermal insulation and temperature control. Detailed Implementation

[0030] The present invention will be further described below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in this technical field.

[0031] Unless otherwise specified, all reagents and materials used in the following examples are commercially available.

[0032] Example 1 1. Raw material preparation (1) Preparation of boron-modified siloxane microcapsules Preparation of the oil phase: Hydroxyl-terminated methylsiloxane, organotin catalyst, trimethyl borate, and Span-80 are mixed and stirred evenly to obtain the oil phase material.

[0033] Preparation of the aqueous phase: Melamine-formaldehyde prepolymer, boric acid, and sodium dodecylbenzenesulfonate were added to deionized water and stirred to dissolve. The pH of the system was adjusted to 7.8 using a weak alkali.

[0034] Emulsification: Slowly pour the oil phase into the aqueous phase system and shear emulsify at 800 r / min for 12 min to form an oil-in-water emulsion; after emulsification, reduce the stirring speed to 275 r / min and continue stirring to stabilize the emulsion state.

[0035] Segmented heating polymerization: The system is heated to 55℃ and held for 1.5 h to polymerize and form the primary capsule wall; the temperature is then increased to 68℃ and held for 3 h, during which the silanol and boronol in the system undergo covalent condensation to generate boron-modified hybrid capsule walls.

[0036] Purification and sieving: The product was aged at room temperature for 4 h, centrifuged to separate the solid product, washed 3 times with deionized water and 1 time with anhydrous ethanol, dried under vacuum at 40℃, and finally sieved to obtain boron-modified siloxane microcapsules with a particle size of 20~50 μm for later use.

[0037] (2) Preparation of trimethylsilyl-terminated silica aerogel Silica aerogel was dispersed in n-hexane with a solid content of 15%; hexamethyldisilazane was added for hydrophobic end-capping modification, and the mixture was stirred at 60°C for 3 h; the mixture was then filtered, air-dried at room temperature, and vacuum-dried at 80°C to obtain trimethylsilyl-terminated silica aerogel for later use.

[0038] 2. Preparation of exterior wall thermal insulation leveling gel (1) Raw material ratio: 48 parts of lithium silicate aqueous solution, 9 parts of hydroxyl-terminated methylsiloxane prepolymer, 14 parts of graded hollow ceramic microspheres, 11 parts of trimethylsilyl-terminated silica aerogel, 4.5 parts of hollow glass microspheres, 3.5 parts of flaky muscovite, 2 parts of nano lanthanum hexaboride, 3 parts of boron-modified siloxane microcapsules, 3.5 parts of lithium magnesium silicate, and 0.6 parts of sodium hexametaphosphate.

[0039] (2) Raw material specifications Lithium silicate aqueous solution: solid content 34%, molar ratio of SiO2 to Li2O 3.6; The number-average molecular weight of the hydroxyl-terminated methylsiloxane prepolymer is 2800; The composition of the graded hollow ceramic microspheres (total mass percentage) is as follows: 70% for 150~200 μm, 18% for 75~150 μm, and 12% for 30~75 μm. Trimethylsilyl-terminated silica aerogel: D90=18 μm; flaky muscovite: D50=7 μm; lanthanum hexaboride particle size 30~80 nm.

[0040] (3) Preparation steps Binder phase premixing: Lithium silicate aqueous solution and hydroxyl-terminated methylsiloxane prepolymer are stirred and mixed evenly at room temperature.

[0041] Vacuum milling modification: Graded hollow ceramic microspheres, aerogel, hollow glass microspheres, muscovite, lanthanum hexaboride, lithium magnesium silicate, and dispersant were added, and vacuum-sealed milling was carried out using 4 mm diameter spherical zirconia milling balls; vacuum degree -0.08 MPa, milling temperature 37℃, milling linear speed 2.85 m / s, and milling time 10 min.

[0042] Low-temperature encapsulation: The sand milling system is naturally cooled to below 40°C, and the boron-modified siloxane microcapsules prepared in step one are added and mixed at low speed.

[0043] Sealed curing: The material is transferred into a sealed container and allowed to stand at a constant temperature of 30°C for 18 hours to obtain the external wall thermal insulation and leveling gel.

[0044] Example 2 1. Raw material preparation (1) Preparation of boron-modified siloxane microcapsules Preparation of the oil phase: Hydroxyl-terminated methylsiloxane, organotin catalyst, trimethyl borate, and Span-60 are mixed and stirred evenly to obtain the oil phase material.

[0045] Preparation of the aqueous phase: Melamine-formaldehyde prepolymer, boric acid, and sodium dodecylbenzenesulfonate are added to deionized water and stirred to dissolve. The pH of the system is adjusted to 7.5 using a weak alkali.

[0046] Emulsification: Slowly pour the oil phase into the aqueous phase system and shear emulsify at 750 r / min for 15 min to form an oil-in-water emulsion; after emulsification, reduce the stirring speed to 250 r / min and continue stirring to stabilize the emulsion state.

[0047] Segmented heating polymerization: The system is heated to 53℃ and held for 1.8 h to polymerize and form the primary capsule wall; the temperature is then increased to 65℃ and held for 3.5 h, during which the silanol and boronol in the system undergo covalent condensation to generate boron-modified hybrid capsule walls.

[0048] Purification and sieving: The product was aged at room temperature for 4 h, centrifuged to separate the solid product, washed 3 times with deionized water and 1 time with anhydrous ethanol, dried under vacuum at 40℃, and finally sieved to obtain boron-modified siloxane microcapsules with a particle size of 20~50 μm for later use.

[0049] (2) Preparation of trimethylsilyl-terminated silica aerogel Silica aerogel was dispersed in n-hexane with a solid content of 15%; hexamethyldisilazane was added for hydrophobic end-capping modification, and the mixture was stirred at 60°C for 3 h; the mixture was then filtered, air-dried at room temperature, and vacuum-dried at 80°C to obtain trimethylsilyl-terminated silica aerogel for later use.

[0050] 2. Preparation of exterior wall thermal insulation leveling gel (1) Raw material ratio: 42 parts of lithium silicate aqueous solution, 8 parts of hydroxyl-terminated methylsiloxane prepolymer, 10 parts of graded hollow ceramic microspheres, 8 parts of trimethylsilyl-terminated silica aerogel, 3 parts of hollow glass microspheres, 2 parts of flaky muscovite, 1 part of nano lanthanum hexaboride, 2 parts of boron-modified siloxane microcapsules, 2 parts of lithium magnesium silicate, and 0.3 parts of sodium hexametaphosphate.

[0051] (2) Raw material specifications Lithium silicate aqueous solution: solid content 32%, molar ratio of SiO2 to Li2O 3.2; The number-average molecular weight of the hydroxyl-terminated methylsiloxane prepolymer is 1200; Composition of graded hollow ceramic microspheres (total mass percentage): 150~200 μm accounts for 65%, 75~150 μm accounts for 22%, and 30~75 μm accounts for 13%; Trimethylsilyl-terminated silica aerogel: D90=15 μm; flaky muscovite: D50=5 μm; lanthanum hexaboride particle size 30~80 nm.

[0052] (3) Preparation steps Binder phase premixing: Lithium silicate aqueous solution and hydroxyl-terminated methylsiloxane prepolymer are stirred and mixed evenly at room temperature.

[0053] Vacuum milling modification: Graded hollow ceramic microspheres, aerogel, hollow glass microspheres, muscovite, lanthanum hexaboride, lithium magnesium silicate, and dispersant were added, and vacuum-sealed milling was carried out using spherical zirconia milling balls with a diameter of 3 mm; vacuum degree -0.06MPa, milling temperature 30℃, milling linear speed 2.5 m / s, and milling time 8 min.

[0054] Low-temperature encapsulation: The sand milling system is naturally cooled to below 40°C, and the boron-modified siloxane microcapsules prepared in step one are added and mixed at low speed.

[0055] Sealed curing: The material is transferred into a sealed container and allowed to stand at a constant temperature of 25°C for 12 hours to obtain the external wall thermal insulation and leveling gel.

[0056] Example 3 1. Raw material preparation (1) Preparation of boron-modified siloxane microcapsules Preparation of the oil phase: Hydroxyl-terminated methylsiloxane, organotin catalyst, trimethyl borate, and Span-60 are mixed and stirred evenly to obtain the oil phase material.

[0057] Preparation of the aqueous phase: Melamine-formaldehyde prepolymer, boric acid, and sodium dodecylbenzenesulfonate are added to deionized water and stirred to dissolve. The pH of the system is adjusted to 8.0 using a weak alkali.

[0058] Emulsification: Slowly pour the oil phase into the aqueous phase system and shear emulsify at 850 r / min for 10 min to form an oil-in-water emulsion; after emulsification, reduce the stirring speed to 300 r / min and continue stirring to stabilize the emulsion state.

[0059] Segmented heating polymerization: The system is heated to 57℃ and held for 1.2 h to polymerize and form the primary capsule wall; the temperature is further increased to 70℃ and held for 2.5 h, during which the silanol and boronol in the system undergo covalent condensation to generate boron-modified hybrid capsule walls.

[0060] Purification and sieving: The product was aged at room temperature for 4 h, centrifuged to separate the solid product, washed 3 times with deionized water and 1 time with anhydrous ethanol, dried under vacuum at 40℃, and finally sieved to obtain boron-modified siloxane microcapsules with a particle size of 20~50 μm for later use.

[0061] (2) Preparation of trimethylsilyl-terminated silica aerogel Silica aerogel was dispersed in n-hexane with a solid content of 15%; hexamethyldisilazane was added for hydrophobic end-capping modification, and the mixture was stirred at 60°C for 3 h; the mixture was then filtered, air-dried at room temperature, and vacuum-dried at 80°C to obtain trimethylsilyl-terminated silica aerogel for later use.

[0062] 2. Preparation of exterior wall thermal insulation leveling gel (1) Raw material ratio: 55 parts of lithium silicate aqueous solution, 10 parts of hydroxyl-terminated methylsiloxane prepolymer, 18 parts of graded hollow ceramic microspheres, 14 parts of trimethylsilyl-terminated silica aerogel, 6 parts of hollow glass microspheres, 5 parts of flaky muscovite, 3 parts of nano lanthanum hexaboride, 4 parts of boron-modified siloxane microcapsules, 5 parts of lithium magnesium silicate, and 1 part of sodium pyrophosphate.

[0063] (2) Raw material specifications Lithium silicate aqueous solution: solid content 35%, molar ratio of SiO2 to Li2O 4.0; The number-average molecular weight of the hydroxyl-terminated methylsiloxane prepolymer is 4500; The composition of the graded hollow ceramic microspheres (total mass percentage) is as follows: 75% for 150~200 μm, 15% for 75~150 μm, and 10% for 30~75 μm. Trimethylsilyl-terminated silica aerogel: D90=15 μm; flaky muscovite: D50=5 μm; lanthanum hexaboride particle size 30~80 nm.

[0064] (3) Preparation steps Binder phase premixing: Lithium silicate aqueous solution and hydroxyl-terminated methylsiloxane prepolymer are stirred and mixed evenly at room temperature.

[0065] Vacuum milling modification: Graded hollow ceramic microspheres, aerogel, hollow glass microspheres, muscovite, lanthanum hexaboride, lithium magnesium silicate, and dispersant were added, and vacuum milling was carried out using 5 mm diameter spherical zirconia milling balls; vacuum degree -0.09 MPa, milling temperature 45℃, milling linear speed 3.2 m / s, and milling time 12 min.

[0066] Low-temperature encapsulation: The sand milling system is naturally cooled to below 40°C, and the boron-modified siloxane microcapsules prepared in step one are added and mixed at low speed.

[0067] Sealed curing: The material is transferred into a sealed container and allowed to stand at a constant temperature of 35℃ for 24 hours to obtain the external wall thermal insulation and leveling gel.

[0068] Example 4 Example 4 has similar technical features to Example 1, except that the vacuum sand milling stage is replaced with 2 mm diameter zirconia grinding balls, and the sand milling time is extended to 20 min.

[0069] Comparative Example 1 Comparative Example 1 has similar technical features to Example 1, except that when preparing the external wall thermal insulation leveling gel, atmospheric pressure stirring for 20 minutes is used instead of vacuum closed sand milling.

[0070] Comparative Example 2 Comparative Example 1 is similar in technical features to Example 1, except that all fillers are modified and dried separately, and are not subsequently milled. The specific operation is as follows: The graded hollow ceramic microspheres and hollow glass microspheres were modified by the following methods: the microspheres were added to an ethanol-water solution (ethanol:water = 1:1) to prepare a suspension with a solid content of 25%; silane coupling agent KH-550 was added at an amount of 1.2% of the mass of the microspheres, and the mixture was stirred at room temperature for 40 min; the mixture was heated to 75℃ and stirred for hydrolysis and grafting for 2 h to graft the coupling agent onto the surface of the microspheres; the mixture was filtered, washed with deionized water to remove the free coupling agent, dried in an oven at 105℃, and sealed for storage until use.

[0071] Flaky muscovite and nano-lanthanum hexaboride were modified by the following methods: aqueous slurries with a solid content of 20% were prepared separately; a small amount of aluminate coupling agent was added to each, and the mixture was stirred and grafted at room temperature for 1.5 h; the mixture was then filtered, washed, and thoroughly dried at 110℃, and stored separately.

[0072] All the individually modified fillers, trimethylsilyl-terminated silica aerogel, lithium magnesium silicate, and inorganic dispersant were added to the already uniformly mixed lithium silicate aqueous solution and hydroxyl-terminated methylsiloxane prepolymer bonding system and stirred at normal pressure for 20 min to mix evenly. The subsequent process and parameters of cooling the system to below 40°C, adding boron-modified siloxane microcapsules, stirring and mixing, and sealing and constant temperature curing were the same as in Example 1.

[0073] Comparative Example 3 The technical solution is similar to that of Comparative Example 2, except that when preparing the external wall thermal insulation and leveling gel, the atmospheric pressure stirring for 20 min is replaced with the vacuum sanding treatment of Example 1.

[0074] Comparative Example 4 The technical solution is similar to that of Example 1, except that no flake muscovite is added.

[0075] Comparative Example 5 The technical solution is similar to that of Example 1, except that the boron-modified siloxane microcapsules are replaced with unmodified siloxane microcapsules, that is, trimethyl borate and boric acid are omitted when preparing the boron-modified siloxane microcapsules.

[0076] Comparative Example 6 The technical solution is similar to that of Example 1, except that the graded hollow ceramic microspheres are replaced with single-particle-size hollow ceramic microspheres with a particle size of 150~200 μm.

[0077] Comparative Example 7 The technical solution is similar to that of Example 1, except that nano-lanthanum hexaboride is replaced with carbon black powder.

[0078] Test methods 1. Basic performance testing The exterior wall thermal insulation and leveling gel prepared in Example 1 was tested according to relevant national standards such as GB 8624-2012, JG / T 24-2018, and GB / T 10294-2008.

[0079] 2. Comparison Test of Differentiated Performance (1) Stability during room temperature storage Each group of gels was sealed and filled into a 1 L plastic bucket and stored at room temperature (25℃) for 90 days. Every 15 days, the phenomena of stratification, sedimentation, clumping, and gel aggregation were observed and the stratification height was recorded. After the observation, the mixture was stirred at a constant speed for 3 minutes to determine whether the precipitate could be evenly dispersed and restored.

[0080] (2) Crack resistance Each group of samples was applied to a cement mortar substrate with a wet film thickness of 5 mm (simulating the construction conditions of thick-layer leveling of external walls). It was cured at room temperature for 7 days to fully cure. The hot and cold cycle regime consisted of freezing at -20℃ for 2 hours and baking at 60℃ for 2 hours as one cycle, for a total of 50 cycles. After the cycle was completed, the number and width of cracks in the coating were observed.

[0081] (3) Temperature rise test of exterior wall under simulated sun exposure According to JG / T 235-2014 Test Method for Thermal Insulation Temperature Difference, uniformly sized cement mortar test panels (150 mm × 150 mm × 10 mm) were used, with each group applying the same wet film thickness of 5 mm, and cured at room temperature for 7 days to achieve complete curing. An artificial solar radiation test chamber was used, with the spectrum matched to AM1.5 standard sunlight, and the total irradiance maintained at a constant 1120 W / m². 2 ±10%; the basic temperature of the environmental chamber is controlled at 25 ℃; a high-precision thermocouple is attached to the center of the back of the test plate, and the highest steady-state temperature of the back of the substrate is recorded after 4 hours of stable irradiation.

[0082] (4) Water immersion resistance Cement mortar test panels of uniform specifications were used. Each group was coated with a 5 mm wet film and cured for 7 days under standard conditions until fully cured. The water immersion operation was carried out in accordance with GB / T 1733-1993. After sealing the sides and back of the test panels, they were completely immersed in tap water at a temperature of 23±2℃ for 14 days. After immersion, the test panels were removed, the surface moisture was absorbed with filter paper, and they were placed in a standard environment for 3 hours. According to GB / T 1766, the appearance defects such as blistering, whitening, chalking, and peeling of the coating were graded and evaluated. Then, the bond strength after immersion was tested according to the pull-out method of GB / T 5210-2018. Finally, the bond strength retention rate before and after immersion of each group was calculated.

[0083] (5) Repair and self-healing properties Prepare cement mortar test panels with a 5 mm wet film and cure them for 7 days. Pre-crack 0.2 mm micro-cracks are made on the surface of the cured coating. Place the panels in a humid and hot environment (temperature 45℃, humidity 85%RH) for 7 days to observe the crack healing and test the bond strength at the healed location.

[0084] Test Results As can be seen from Table 1, all indicators of Example 1 meet the standards, and the performance of Examples 2 and 3 is similar to that of Example 1, indicating that the proportions and sand milling process range of the present invention are stable and reliable.

[0085] Conventional lithium silicate slurry requires separate pretreatment of fillers with coupling agents, and sand milling only serves a simple dispersion function. However, this invention utilizes the controlled friction of vacuum sand milling to simultaneously activate the filler and binder hydroxyl groups, achieving in-situ covalent condensation to form an organic-inorganic interpenetrating network matrix without a separate modification stage. This improves upon the tendency of pure lithium silicate to shrink and crack, unlike conventional methods that simply add fibers or emulsions for physical toughening. A continuous thermal insulation framework is constructed using graded hollow microspheres, sheet-like mica disperses shrinkage stress, and lithium magnesium silicate regulates the rheology of the paste. The filler and matrix interface are tightly bonded, effectively solving the problem of filler agglomeration and sedimentation during long-term static placement. Example 1 shows rapid surface drying, smooth thick-layer construction, a thermal conductivity as low as 0.028 W / (m·K), and VOC and formaldehyde content far below national standards. It achieves an A (A2) non-combustible rating, and its adhesion and compressive strength meet the requirements for exterior wall leveling.

[0086] Table 1. Basic performance test results of Example 1

[0087] Example 1 uses 4 mm zirconia grinding balls and vacuum sand milling for 8-12 min. The grinding and friction simultaneously achieve in-situ hydroxyl bonding modification of the filler and covalent cross-linking of lithium silicate-siloxane. The closed cavity of the hierarchical hollow microspheres is completely preserved. Combined with sheet-like muscovite to disperse shrinkage stress and boron-modified siloxane microcapsules to provide secondary cross-linking repair capability, the triple heat insulation filler works together to block conduction, convection and infrared radiation heat. Therefore, after 90 days of storage, there is almost no delamination, the 5 mm thick layer has no cracks after cold and heat cycles, the lowest thermal conductivity, the water immersion adhesion retention rate and crack self-healing strength are all at the optimal level, and the substrate temperature rise is the lowest under simulated irradiation.

[0088] Example 4 only increased the grinding intensity, replaced the 2 mm zirconia grinding balls and extended the grinding time to 20 min. Excessive impact and shearing directly crushed the graded hollow ceramic microspheres and hollow glass microspheres, destroying a large number of sealed air cavities in the heat insulation skeleton and significantly increasing the thermal conductivity. At the same time, the hydroxyl groups in the system were over-activated, the cross-linking reaction was unbalanced, the internal stress was concentrated after the coating was cured, and microcracks were generated by thermal cycling. The original interfacial bonding structure of the filler was destroyed by strong grinding, the interfacial bonding force decreased, the strength retention rate and crack self-healing ability were worse after immersion in water, and the thickness of the filler sedimentation and delamination increased significantly during storage.

[0089] Comparative Example 1 only uses atmospheric pressure stirring, without strong friction, which makes it impossible to peel off the inert adsorption layer on the surface of the filler. The filler and the binder phase are only physically mixed, without covalent interface bonding. The lithium and silicon phases are difficult to fully dehydrate and condense to form a dense interpenetrating network. The fillers of different densities in the slurry lack chemical bond anchoring constraints, and after long-term static placement, they quickly settle and clump together, which is difficult to restore by stirring. The cross-linking degree of the cured matrix is ​​insufficient, the waterproof and dense properties are poor, the strength decreases significantly after immersion in water, the thermal shrinkage stress of the thick coating cannot be effectively buffered, a large number of obvious cracks are generated on the surface, the complete triple thermal insulation synergistic system cannot be stably formed, and the overall thermal insulation and cooling performance is weak.

[0090] Comparative Example 2 uses a traditional off-site coupling modification and drying process followed by atmospheric pressure mixing. When the dried modified filler is remixed into the bonding system, it is prone to secondary agglomeration. There are a large number of interfacial gaps between the filler and the matrix, increasing the heat conduction channels and simultaneously reducing the thermal insulation and water resistance properties. The coupling agent only relies on physical adsorption to coat the filler surface, resulting in weak interfacial bonding. During long-term storage, the filler continues to settle and stratify, and the number of shrinkage cracks increases significantly after curing, leading to a decrease in overall comprehensive performance.

[0091] The grinding and shearing of Comparative Example 3 directly scrapes off the silane and aluminate coupling agent coating layer pre-grafted on the filler surface, rendering the previous filler modification process completely ineffective. Although it has a certain cross-linking effect, it lacks a stable interface structure formed by in-situ hydroxyl condensation, and the filler will still slowly settle. Its various properties cannot reach the excellent level of integrated grinding modification of this invention.

[0092] In Comparative Example 4, the removal of flaky muscovite resulted in the absence of layered and flaky fillers that dispersed the curing shrinkage stress and blocked internal heat convection. Consequently, the coating curing shrinkage stress became concentrated, and clear shrinkage cracks appeared on the edges and surface after thermal cycling. Internal heat convection intensified, and the thermal conductivity increased synchronously with the temperature rise of the exposed substrate. Water resistance and self-healing properties also showed a slight decrease.

[0093] Comparative Example 5 replaced ordinary boron-free siloxane microcapsules. The capsule wall did not have a boron-silicon hybrid cross-linking structure. After the crack opened, it could only rely on simple physical adhesion of siloxane and could not undergo secondary covalent condensation reinforcement with the matrix. The mechanical strength recovery rate at the crack healing site was greatly reduced. Other basic thermal insulation and storage performance had no obvious defects, only lacking the core advantage of long-term self-healing protection.

[0094] Comparative Example 6 replaced the graded hollow ceramic microspheres with single 150~200 μm microspheres. The filler packing void ratio was unbalanced, the number of continuous thermal bridges inside the skeleton increased, the proportion of closed still air decreased, and the thermal conductivity increased significantly. The single-size particles had uneven packing shrinkage, and after curing, the coating collapsed and multiple cracks were generated, and the thermal insulation and crack resistance deteriorated simultaneously.

[0095] Comparative Example 7 uses carbon black powder instead of nano-lanthanum hexaboride. Carbon black does not have the function of selectively blocking near-infrared radiation. Instead, it absorbs a large amount of solar radiation heat, and the temperature on the back of the substrate is significantly higher in the artificial irradiation test. Carbon black particles have no low-radiation heat insulation effect, which destroys the synergistic system of conduction-convection-infrared triple heat insulation, and the overall cooling and heat insulation effect is greatly weakened.

[0096] Table 2. Results of Differentiated Performance Comparison Tests

[0097] Based on all the data, it can be seen that the vacuum sand milling integrated in-situ modification process, the graded thermal insulation filler compound, the flaky muscovite, the boron-modified self-healing microcapsules, and the nano-lanthanum hexaboride synergistic system of the present invention work together to achieve multiple advantages such as long-term stable storage, thick-layer cold and heat crack resistance, low thermal conductivity insulation, long-term water resistance, crack self-healing, and external wall thermal insulation and cooling. These comprehensive technical effects cannot be achieved by existing single formulas or conventional preparation processes.

[0098] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. An external wall thermal insulation and leveling gel, characterized in that, By weight, it includes the following components: 42-55 parts of lithium silicate aqueous solution, 8-10 parts of hydroxyl-terminated methylsiloxane prepolymer, 10-18 parts of graded hollow ceramic microspheres, 8-14 parts of trimethylsilyl-terminated silica aerogel, 3-6 parts of hollow glass microspheres, 2-5 parts of flaky muscovite, 1-3 parts of nano-lanthanum hexaboride, 2-4 parts of boron-modified siloxane microcapsules, 2-5 parts of lithium magnesium silicate, and 0.3-1 parts of inorganic dispersant.

2. The external wall thermal insulation and leveling gel according to claim 1, characterized in that, In the external wall thermal insulation and leveling gel, graded hollow ceramic microspheres and hollow glass microspheres come into contact with each other to form a skeleton structure, and sheet-like white mica is interspersed in the gaps of the skeleton structure; lithium silicate aqueous solution and hydroxyl-terminated methylsiloxane prepolymer are covalently condensed to form an interpenetrating network adhesive matrix.

3. The external wall thermal insulation and leveling gel according to claim 1, characterized in that, The graded hollow ceramic microspheres contain the following particle sizes: 150~200 μm, 75~150 μm, and 30~75 μm.

4. The external wall thermal insulation and leveling gel according to claim 1, characterized in that, The solid mass fraction of the lithium silicate aqueous solution is 32%~35%, and the molar ratio of silicon dioxide to lithium oxide is 3.2~4.

0.

5. The external wall thermal insulation and leveling gel according to claim 1, characterized in that, The number-average molecular weight of the hydroxyl-terminated methylsiloxane prepolymer is 1200~4500.

6. A method for preparing the external wall thermal insulation and leveling gel according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Stir and mix the lithium silicate aqueous solution and hydroxyl-terminated methylsiloxane prepolymer until homogeneous; S2. Add graded hollow ceramic microspheres, trimethylsilyl-terminated silica aerogel, hollow glass microspheres, flake mica, nano lanthanum hexaboride, lithium magnesium silicate, and inorganic dispersing agents, and perform vacuum closed sand milling using zirconia grinding balls with a particle size of 3~5 mm. S3. After cooling the system, add boron-modified siloxane microcapsules and stir to mix. S4. Sealed and constant temperature curing to obtain external wall thermal insulation and leveling gel.

7. The preparation method of the external wall thermal insulation and leveling gel according to claim 6, characterized in that, The linear speed of the S2 vacuum sand mill is 2.5~3.2 m / s, and the sand milling time is 8~12 min.

8. The preparation method of the external wall thermal insulation and leveling gel according to claim 6, characterized in that, The preparation method of the boron-modified siloxane microcapsules includes the following steps: hydroxyl-terminated methylsiloxane, organotin catalyst, trimethyl borate, and oil phase emulsifier are mixed evenly to obtain an oil phase; melamine-formaldehyde prepolymer, boric acid, and anionic emulsifier are dissolved in deionized water, and the pH of the system is adjusted to 7.5-8.0 to obtain an aqueous phase; the oil phase is added to the aqueous phase, and shear emulsification is performed to form an oil-in-water emulsion, which is then stirred to stabilize the emulsion system; staged heating polymerization is performed to first form a primary capsule wall, and then the silanol and boronol groups in the system undergo covalent condensation to form a hybrid capsule wall; after purification and sieving, the boron-modified siloxane microcapsules are obtained.

9. The preparation method of the external wall thermal insulation and leveling gel according to claim 8, characterized in that, First, heat to 53~57℃ and hold for 1.2~1.8 h to form the primary capsule wall, then heat to 65~70℃ and hold for 2.5~3.5 h to carry out covalent condensation of silanol and boronol.

10. The preparation method of the external wall thermal insulation and leveling gel according to claim 8, characterized in that, The shear emulsification speed is 750~850 r / min, and the emulsification time is 10~15 min; the stirring speed of the stabilized emulsion is 250~300 r / min.

Citation Information

Patent Citations

  • Inorganic silicon sound insulation and heat preservation gel and manufacturing method thereof

    CN117229678A